Misinterpretation of the Hadith of Luzūm Al-Jamā'ah and Its Impact on Social Interaction within the LDII Community in Samarinda City - Abdul Majid (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
This article aims to describe LDII's understanding of the hadith about being consistent with the congregation, analyze their understanding concerning the understanding of scholars, and describe the impact of this understanding on their social interactions with the general public. The research method is quantitative with a phenomenological analytical descriptive approach. They obtained the data through interviews with four categories.: LDII administrators/mullahs, former LDII members,